Motor symptoms and the quality of life of relapsing-remitting multiple sclerosis patients in a specialized center in South of Brazil - Jorge, Francielle Fontana; Finkelsztejn, Alessandro; Rodrigues, Luciano Palmeiro (Arquivos de Neuro-Psiquiatria, 2021)
Background: Spasticity, fatigue, muscle weakness and changes in gait are some of the main motor symptoms of Multiple Sclerosis (MS). These changes can interfere with the patients’ quality of life. Objective: To characterize the motor and quality of life symptoms in patients with relapsing-remitting Multiple Sclerosis at a specialized center. Methods: Fifty five patients at the Neuroimmunology Outpatient Clinic of the Hospital de Clínicas de Porto Alegre were evaluated for fatigue (Fatigue Severity Scale — FSS), walking ability (Functional Ambulation Categories — FAC), impact of MS on walking (Multiple Sclerosis Walking Scale-12 — MSWS-12), walking speed (10-Meter Walk Test — 10MWT and the Times 25-foot Walk test — T25FW), functional independence (Barthel Index — BI), functional mobility (Timed Up and Go — TUG), and quality of life (Multiple Sclerosis Impact Scale — MSIS-29). Results: The patients were mostly women (69.1%), with average age of 43.3 (±12.1) years old, with time since diagnosis of 8.2 (±5.3) years, and EDSS average of 4.3 (±1.3). On the BI, the mean was 96.6 (±5.7) points and 80% of the patients had FAC 5. At MSIS-29, patients had a higher average score on the psychological scale (19.5±26.7) than on the physical scale (10.2±23.6). Most patients (69.1%) presented fatigue. Conclusion: The patients had preserved functional independence and functional walking ability and presence of fatigue. There was minimal impact of MS on patients’ quality of life.
Keywords: Multiple Sclerosis; Fatigue; Gait; Quality of Life